Cover, Content, and Editorial Note from Borneo J Pharm Vol. 5 No. 3 August 2022 - Chief Editor of Borneo J Pharm (Borneo Journal of Pharmacy, 2022)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of the Borneo Journal of Pharmacy (Borneo J Pharm), has been published at August 2022. This edition contains ten articles: Pharmacognosy-Phytochemistry, Pharmaceutical, Microbiology Pharmacy, Natural Product Development, Clinical-Community Pharmacy, and Management Pharmacy. This edition includes writings from four countries: Costa Rica, India, Indonesia, Netherlands, and Nigeria. The authors come from several institutions, including Universitas Ahmad Dahlan, K24 Indonesia, Institut Sains dan Teknologi Nasional, Universidad de Costa Rica, Kebbi State University of Science and Technology, Aliero, Federal University, Birnin Kebbi, Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, IPB University, National Research and Innovation Agency Republic of Indonesia, Poltekkes Kemenkes Bandung, Sekolah Tinggi Ilmu Farmasi Riau, Universitas Islam Negeri Maulana Malik Ibrahim, Universitas Airlangga, Universitas Hang Tuah, Universitas Katolik Widya Mandira, University of Groningen, Universitas Gadjah Mada, Universitas Hasanuddin, Universitas Syiah Kuala, Poltekkes Kemenkes Maluku, and Universitas Islam Sultan Agung. Editorial boards are fully aware that there are still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repetoire in this issue. We hope that all parties, especially the contributors, could re-participate for the publication in the next edition on November 2022. Wassalamu’alaikum Wr. Wb.